An Error Analysis of Preposition in Student's Recount Text: A Descriptive Study at MAN 2 Padang - Ika Nur Islami; Witri Oktavia (Universitas Negeri Padang, 2020)
This study aimed to identify, classify and explain the errors and source of error that the second grade students of MAN 2 Padang made in using preposition based on surface strategy taxonomy and Brown’s theory (2000). The instrumentation of this research is recount text. In this research, the researcher uses a qualitative descriptive method. The researcher reveals the types of errors and explains the sources of error that occurred. The result of the research shows that 144 errors occurred at the second grade students of Man 2 Padang in using preposition. The researcher found the highest percentage of type of error is misformation with total number 78 errors or 54,16%. The other finding is sources of errors which has interlingual transfer as the highest soure of error with total number 114 error or 79,16%.